ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH DIBERLAKUKANNYA TAX AMNESTY PERIODE KETIGA TAHUN 2016 PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI - Rina Ariani; Afifudin Afifudin; Muhammad Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine the financial performance before and after thetax enacted in 2016 in companies and industries. The population in this researchis textile and germent sub-sector. Sampling was done by purposive samplingtechnique and obtained by 10 sample companies. The data used is secondary datain the form of financial statements of the second quarter of 2016 and secondquarter of 2017 using the website www.idx.co.id Hypothesis testing is done bypaired sample t-test. The results show before taxes and taxes used in the currentratio of current ratio, Debt to Equity Ratio, Total Assets Turn Over and ReturnOn Equity there are significant differences CR, DER, TATO and ROE before andafter the enactment of tax amnesty third period ,Keywork : Tax Amnesty, Current Ratio, Debt To Equity Ratio, Total Assets TurnOver, Return On Equity